Love Is Power or Something Like That - Barrett, A. Igoni (Kachifo Ltd, 2013)
A family's fortunes fall from love and wealth to infidelity and poverty as poor choices unfurl over three generations. With humor and tenderness, Barrett introduces us to an utterly modern Nigeria, where desire is a means to an end, and love is a power as real as money.
Keywords: Fiction; Short Stories